Connection status report generator - Pratyush Gupta; Somnath Banerjee; Debani Prasad Mishra; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2021)
This paper presents “Connection Status Report Generator” which is an auto executable application and it generates a detailed textual and pictorial representation of the network connectivity status of a particular computer and sends the generated reports to the concerned party. The features developed in this paper aim to constantly monitor the network connectivity status as well as ease the troubleshooting process of finding the major cause of call-drops which is a popular problem in every industry. This paper is divided into three major sub-categories of real-time connection status tracker, report generator, and the image viewer interface. The proposed executable application is coded in Java and designed to run as a background application with minimal system prerequisites.